Temporal patterns in coral reef, seagrass and mangrove communities from Chengue bay CARICOMP site (Colombia): 1993-2008 - Alberto Rodríguez-Ramírez; Jaime Garzón-Ferreira; Angélica Batista-Morales; Diego L. Gil; Diana Isabel Gómez-López; Kelly Gómez-Campo; Tomás López-Londoño; Raúl Navas-Camacho; María Catalina Reyes-Nivia; Johanna Vega-Sequeda (Revista de Biología Tropical, 2010)
Few monitoring programs have simultaneously assessed the dynamics of linked marine ecosystems (coral reefs, seagrass beds and mangroves) to document their temporal and spatial variability. Based on CARICOMP protocol we evaluated permanent stations in coral reefs, seagrass beds and mangroves from 1993 to 2008 in Chengue Bay at the Tayrona Natural Park, Colombian Caribbean. Overall, the studied ecosystems showed a remarkable stability pattern over the monitoring period. While there were annual variations in coral reefs (coral cover) and mangroves (litterfall) caused by hurricane Lenny in 1999, particular trends in seagrass (leaf area index and leaf productivity) appear to reflect the natural variability in this ecosystem. We suggest that monitoring sites at the three marine ecosystems had in general a healthy development in the last 16 years. Our results are critical to locally improve the management strategies (Tayrona Natural Park) and to understand the long-term dynamics of closely associated marine ecosystems in the Caribbean. Rev. Biol. Trop. 58 (Suppl. 3): 45-62. Epub 2010 October 01. Pocos programas de monitoreo han estudiado simultáneamente la dinámica de ecosistemas marinos estrechamente relacionados (arrecifes coralinos, pastos marinos y manglares) para documentar su variabilidad espacial y temporal. Siguiendo el protocolo de monitoreo del programa CARICOMP, estaciones permanentes de monitoreo en estos ecosistemas fueron evaluadas entre 1993 y 2008 en la Bahía de Chengue del Parque Nacional Natural Tayrona (Caribe Colombiano). En general los ecosistemas monitoreados han presentado un patrón de estabilidad durante los años de estudio. Mientras los arrecifes coralinos (cobertura de coral) y manglares tuvieron algunas variaciones anuales debidas al paso del huracán Lenny en 1999, los pastos marinos registraron tendencias particulares de cambio (índicece de área foliar y productividad de hojas) que podrían estar reflejando la variabilidad natural de la pradera estudiada.Por lo tanto se sugiere que los sitios monitoreados en cada ecosistema han tenido un desarrollo saludable en los últimos 16 años. Estos resultados son importantes para mejorar localmente las estrategias de manejo (Parque Nacional Natural Tayrona) y para evaluar la dinámica a largo plazo en los ecosistemas marinos del Caribe.